Effect of ceramic materials and tooth preparation design on computer‐aided design and computer‐aided manufacturing endocrown adaptation and retentive strength: An in vitro study - Ahmed Farghal; Karim Dewedar; Mohammed H. AbdElaziz; Samah Saker; Mahy Hassona; Radwan Algabri; Ahmed Yaseen Alqutaibi (Wiley, 2024)
Abstract Objectives To evaluate how various tooth preparation designs impact the adaptation-both at the margins and internally-and the retentive strength of computer‐aided design and computer‐aided manufacturing (CAD/CAM) produced endocrowns. Materials and Methods 60 extracted human mandibular first molars were endodontically treated and assigned into three groups (n = 20) according to the tooth preparation design: Group N: butt joint design, Group F and F1 received 1‐ and 2‐mm circumferential ferrule preparation, respectively. Endocrowns were milled using either lithium disilicate glass‐ceramic (IPS emax ceramic) or monolithic zirconia. The internal and marginal adaptation of the endocrowns were evaluated using the replica technique. After cementation, the endocrowns of all test groups were dislodged axially at 0.5 mm/min using a universal testing machine. A 2‐way ANOVA and the independent samples t‐test (α = .05) were performed to statistically analyze the data. Results The effect of changing the design of the tooth preparation (butt joint, ferrule) on the marginal and internal gap was shown to be statistically significant (p < .05); the lower gap values were recorded at the axial followed by cervical, marginal, and pulpal floor walls in both ceramic groups regardless of the teeth preparation design. The ANOVA test revealed similar average removal forces and stresses for the two types of tested ceramic materials. Conclusion IPS emax ceramic adapted better than monolithic zirconia ceramic, regardless of the preparation design. Ferrule preparation design is more retentive than butt joint preparation, regardless of the type of ceramic material used.